The Absence of Psychosocial Services in Indonesian Primary Schools: A Systematic Literature Review - Kusumaningrum, Ika Muharini; Rusdarti, Rusdarti; Widodo, Joko (Proceedings of International Conference on Science, Education, and Technology, 2025)
Psychosocial services in primary schools are vital for a more inclusive and equitable education but still remain largely absent within Indonesia, for they cause an important gap when they do not quite meet children’s emotional and behavioral needs. This study aims to examine the urgency and relevance of psychosocial support in Indonesian primary education. Using a systematic literature review of national and international journals published between 2020 and 2025, the study synthesizes empirical findings on children’s psychosocial development, the roles and limitations of primary school teachers, and effective school-based mental health interventions globally. Results reveal that the lack of structured psychosocial services affects children’s emotional well-being negatively. Addressing these issues also places an unsustainable burden upon untrained teachers. A comparative analysis of countries such as Finland, South Korea, and South Africa highlights some successful models that integrate mental health support within the school systems. Indonesia risks obstructing holistic young learner development without urgent policy changes, teacher capacity building, and strong school-community collaboration, the study concludes. Key recommendations include teachers implementing basic psychosocial training, school communities establishing collaborative networks, and integrating mental health policies within national education frameworks to promote sustainable and inclusive primary education.